ANALISIS KEUNTUNGAN USAHATANI BAWANG DAUN DI DESA BONGKUDAI UTARA KECAMATAN MOOAT KABUPATEN BOLAANG MONGONDOW TIMUR - Mamusung, Elsa Novera; Rengkung, Leonardus Ricky; Talumingan, Celcius . (AGRI-SOSIOEKONOMI, 2019)
This study aims to analyze how much profit the farmers get in the activities of scallionÂ farming in North Bongkudai Village, Mooat District, East Bolaang Mongondow Regency. The studyÂ was conducted for 3 months from October to December 2018. The data used in this study wereÂ primary data and secondary data. Primary data collection is through direct interviews with 60Â respondents using the stratified random sampling method. Interviews were conducted based on aÂ previously prepared questionnaire, and secondary data was obtained from the Bolaang MongondowÂ East Agriculture Office, North Bongkudai Village Office, Sam Ratulangi University Faculty ofÂ Agriculture Library, and Local Book Stores. The analysis in this study is qualitative and quantitative analysis presented in table form and then described descriptively. The results showed that theÂ amount of profit of the scallion farmers per bed in Bongkudai Utara village in the first strata (lowerÂ layer) was Rp.426,664, while for the second strata (middle layer) was Rp.439,185 and for the thirdÂ strata (upper layer) was Rp. 1,227,853. The highest profit of scallion farmers in Bongkudai UtaraÂ Village is in the third strata, reaching Rp1,227,853 per bed.*lrr+eprm*